A CONTENT ANALYSIS OF THE ENGLISH TEXTBOOKS USED AT JUNIOR HIGH SCHOOL (A STUDY ON HOW TEACHERS PERCEIVE THE CONTENT OF THE TEXTBOOKS) - Gumelar, Ginanjar Sukma (2015)
The aim of this study is to find out the fulfillment of the most used English textbooks for state junior high school to the criteria of ideal textbooks as perceived by English teachers and find out the strength and weakness of the textbooks. To achieve these objectives, the study employed qualitative and quantitative research methods. The data were obtained from the checklist formulated from BSNP standard. The checklist was distributed to English teachers to analyze content of the textbooks. The data were quantified, but then analyzed interpretatively rather than statistically. The result of this study shows out that the textbooks fulfill the criteria and are suitable for the learners. However, this textbook series has weaknesses in graphical aspects, which is usually considered as the most attractive aspect for junior high school students.